1998
DOI: 10.4315/0362-028x-61.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Heat Resistance of Alicyclobacillus acidoterrestris Spores as Affected by Various pH Values and Organic Acids

Abstract: Alicyclobacillus acidoterrestris, a thermoacidophilic sporeformer, has caused spoilage of fruit juices which had been treated with thermal processes intended to commercially sterilize the juice. The objective of this research was to document the effect of pH, acid, and temperature on the heat resistance of spores of three fruit-juice isolates of A. acidoterrestris. The thermal resistance of spores of A. acidoterrestris strains VF, WAC, and IP were studied in a model fruit-juice system composed of 12% glucose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
50
1
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 0 publications
4
50
1
2
Order By: Relevance
“…Heat resistance studies have indicated that Alicyclobacillus spores can survive the usual hot-fill processes that are used with commercial juices (4,5,14,(24)(25)(26)(27). Data also indicate that increasing the uBrix makes the spores more resistant to heat.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Heat resistance studies have indicated that Alicyclobacillus spores can survive the usual hot-fill processes that are used with commercial juices (4,5,14,(24)(25)(26)(27). Data also indicate that increasing the uBrix makes the spores more resistant to heat.…”
Section: Resultsmentioning
confidence: 71%
“…Data also indicate that increasing the uBrix makes the spores more resistant to heat. Although the reason Alicyclobacillus spores survive pasteurization and hot-fill and hold processes is still unclear, environmental factors such as pH, soluble solid content, and temperature influence the heat resistance of the spores (10,25,27). D-values for spores of different strains of A. acidoterrestris at 80, 85, 90, and 95uC in conventionally heated fruit juices were 41.1 to 54.3, 50 to 65.6, 7.4 to 23, and 2.3 to 5.3 min, respectively, with zvalues of 7.7 to 12.9uC (3-5, 14, 25-27).…”
Section: Resultsmentioning
confidence: 99%
“…are commonly present on the soil and may be detected by fine-tuned isolation and culture methodologies that are specific to their nutritional and mineral requirements (Motohiro;Hiroko, 1994). As the thermal resistance of spores may be affected by media composition, ions, pH and organic acids, detection may be conducted in several different ways (Pontius et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Without a perfectly closed system or the ability to control the concentration of oxygen in the bottle, it is impossible to evaluate the effect of oxygen concentration on cell division in culture experiments, and there are no known reports of such Alicyclobacillus spp. are spore-forming and heattolerant acidophilic bacilli that survive a typical sterilization process of 85 for more than 30 min in bottled acidic beverages, such as fruit juices and sport drinks, and cause deterioration Pettipher et al,1997;Pontius et al,1998 . Among the species in this genus, A. acidoterrestris is regarded as one of the most harmful bacteria in acidic beverages, and it produces guaiacol, which has a creosote-like odor.…”
mentioning
confidence: 99%